(untitled) (American Journal of Islam and Society, 1997)
In Islamabad, while speakers at a recent OIC/Comstech (Standing Committee on Science and Technology) meeting titled “Science in the Islamic Polity in the Next Century” delivered tirades against the West, they conspicuously stood at a podium that boldly displayed the words “Best Western.’” This postmodern paradox captures the angst of a conference that called for more basic science; more and better textbooks; a science focused on the basic human needs of food, shelter, and energy; a self-sustaining science, independent of external money or models; a “Big Western” science that develops new laser, information, and nuclear technologies; and a science that better reflects the worldview of Islam. Amidst calls for transformation, even by individuals who had been at the helm of the scientific establishment for the last twenty years, it was clear that science in Muslim nations, particularly Pakistan, had gone in the wrong direction. Even the “correct” decisions resulted in disaster because of science policies committed to “big science.” While nations like Malaysia focused on products that had commercial gain or ensured the reduction of power of the feudal class, most Muslim nations remained committed to self-aggrandizement and war (both imaginary and real) with their neighbors. Instead of developing commercial science or local science that could meet basic needs and create better health conditions for women and children, nuclear strategies or “big science” was paramount. The costs incurred by the Muslim nations are now quite evident- terrifyingly low literacy rates, the low number of high school and college graduates, the high number of people suffering from malnutrition, to mention but a few obvious indicators. It seems the effects of external and internal colonialism remain, as do pre-Islamic dynastic battles. In the midst of the utter failure of “big science” or “western science," ...